Designing a Marking Scheme to Assess the Performance of TE Basic Students at ILP - Alvin Taufik (Journal of English Language and Culture, 2017)
The aim of this project work is to design a marking scheme that will be used in assessing the performance of Talking English (TE) Basic students in ILP. The scheme was designed using the stages proposed by Mertler (2001). The stages start with the process of deciding the aim of marking scheme creation in order to acknowledge the importance of the proposed scheme. It is then continued with the process of deciding the object of the assessment, the type, criteria, scale and performance description of the scheme. The steps end with the testing of the scheme. The tested scheme is perfected through discussion of the results of the testing. The criteria of the scheme are formulated based on the concept of Communicative Language Ability as proposed by Bachman (1990). Based on the formulation, the writer has created a descriptive based marking scheme which distribution is done daily through the use of check list method. Keywords: Marking Scheme, Communicative Language Ability, Performance